1985
DOI: 10.1039/an9851001111
|View full text |Cite
|
Sign up to set email alerts
|

Analytical investigations of cephalosporins. Part 9. Polarographic behaviour of some selected cephalosporins and assay of their formulations

Abstract: The polarographic properties of cephalothin, cephacetrile, cefamandole, cefamandole nafate and cefoperazone were investigated by using cathode-ray polarography (CRP) and differential-pulse polarography (DPP). The electroactive group present in the investigated cephalosporins is the R' leaving group in CH2R', which is located at the 3-position. The electrochemical methods developed were applied to cephalosporins in dosage forms and a comparison was made with the Ni(ll)hydroxylamine method. The relative standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Based on chemical (31) and electrochemical (29,(32)(33)(34)(35) reduction results, this wave has been attributed to the reductive elimination of the substitute on the 3-methylene group (29,(32)(33)(34)(35). The half-wave reduction potential for this wave has been reported as highly dependent upon pH, shifting to more negative potentials as pH increases (26,28,29,32), with the diffusion current decreasing dramatically (25,27,32). Hall et al (32) have observed a shift in half-wave potential from approximately −0.96 V to about −1.55 V for a single reduction wave for cephalothin, as pH changed from very acidic to neutral.…”
Section: Discussionmentioning
confidence: 94%
“…Based on chemical (31) and electrochemical (29,(32)(33)(34)(35) reduction results, this wave has been attributed to the reductive elimination of the substitute on the 3-methylene group (29,(32)(33)(34)(35). The half-wave reduction potential for this wave has been reported as highly dependent upon pH, shifting to more negative potentials as pH increases (26,28,29,32), with the diffusion current decreasing dramatically (25,27,32). Hall et al (32) have observed a shift in half-wave potential from approximately −0.96 V to about −1.55 V for a single reduction wave for cephalothin, as pH changed from very acidic to neutral.…”
Section: Discussionmentioning
confidence: 94%
“…Differential pulse voltammograms for the reduction of CFX at a HDME in absence and presence of Cu 2+ ion are shown in Figure 2. The recorded differential pulse peak (Figure 2 , curve 2 ) for the reduction of CFX at −0.65 V is mainly due to the reduction of ‐CH 2 OCONH 2 group located at the C3 position [22] . A pure Cu 2+ containing solution (Figure 2, curve 1) exhibits only a single reduction peak at a potential of‐0.5 V. However, the addition of Cu 2+ to a solution of CFX (1 : 1) resulted in the disappearance of the cathodic reduction of CFX at −0.65 V and the appearance of new well‐defined peak at −0.93 V (Figure 2 , curve 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Polarograms of CFZ in B-R buffers of pH 2-11 exhibited a single 2-electron irreversible cathodic wave with almost pHindependent limiting current which could be due to the reduction of the -CH 2 S-moiety of CFZ molecule [21,[23][24][25][26].…”
Section: Dc-polarographymentioning
confidence: 98%